Cancer in an Historic Washington DC African American Population and Its Geospatial Distribution - Jackson, Latifa; Jackson, Hasan; Mohammed, Mariam; Guthrie, Nicholas; Kim, Shihyun; Okolo, Rita; Jackson, Fatimah (Frontiers in Oncology, 2018)
Background: Cancer continues to be a major cause of morbidity and mortality in the African American community but insights into the types and incidence of cancer 85 years ago have been virtually non-existent and little is known of its geospatial distribution. Historical information on cancer can shed light on current health disparities, particularly among African Americans. Objective: The aims of this study were to: 1) assess the frequencies of the cancer types present among Cobb Collection individuals; 2) compare these data with current research on cancer in African Americans; and 3) evaluate the pattern of cancer expression, including its geospatial distributions, as a cause of death between 1931-1969 in an historic African American subgroup and compare this pattern with the historic and contemporary patterns of cancer etiology and incidence. Methods: Systematic assessments of the existing clinical, demographic, and anatomical records in the Cobb Research Laboratory were made of individuals identified as dying from specific cancers from 1931-1969. These were compared with the national profiles of cancer during the historic time an individual died as well as the contemporary patterns of cancer deaths. Analysis of their residential addresses just prior to death were assessed using a commercial geographic information system. Each location was assigned a geospatial location and proximity between each site and clusters of sites were investigated. Results: 17 different cancer types were found within 28 individuals of the Cobb Collection between 1931 and 1969. The cancer types with the highest frequencies were carcinoma of stomach, lung, esophagus, larynx and bronchogenic carcinoma. 84% of all cancer incidents occurred in males and 76% were among individuals identified as African American. 71% of the highest incidence cancers were among African American males. Geospatial clustering was observed most noticeably in the redistribution of carcinoma of the esophagus. Conclusion: Our results provide historical depth to our knowledge of the common cancer causes of morbidity among African Americans of Washington DC from 1931-1969. We contrast these findings with national historical data on cancer etiology and ethnic disparities in incidence. Our study suggests that historic data can provide longitudinal depth to our understanding of the persistence